ESTIMATING THE SHEAR STRENGTH OF SISAL FIBRE REINFORCED CONCRETE (Nigerian Journal of Technology, 2019)
This research examines the shear strength of Sisal Fibre Reinforced Concrete (SSFRC).Sisal Fibre (SSF) addition was at 1% by weight of dry constituents, this is considered the upper limit for workable mixes in the absence of water reducing agents. Beams of various grades of concrete (20N/mm2 to 40N/mm2) were tested and they all failed in shear. Experimental results of beams were compared with modified versions of the BS 8110 formula for shear strength in concrete, to determine the best fit. The inclusion of SSF at 1% addition increased the compressive strength of the concrete mix by an average of 16.9% and the shear strength by 16%. However, the shear strengths of the SFRC are only greater than those of normal concrete of corresponding compressive strengths by 9.5%. The equation proposed may be used to estimate the shear strength of SSF reinforced concrete at this level of fibre addition.  http://dx.doi.org/10.4314/njt.v38i3.3